Optimasi Sistem Antrian M/G/C dan Penerapannya Pada Pelayanan Servis Sepeda Motor - Ririn Dehi; Achmad, Novianita; Wiranto, Ifan (Research in the Mathematical and Natural Sciences, 2023)
This study discusses the performance of the queuing system in optimizing service at motorcycle service. This research was conducted at PT. Hasjrat Abadi-Yamaha Gorontalo, the research was conducted by taking primary data for 27 days at 08.00 - 12.00. The variables used are customer arrival time data and customer service time. The results showed that the queuing system at the motorcycle service station is the arrival time distribution, namely the Poisson distribution, while the service time distribution is the general distribution. So the queuing system at the motorcycle service center follows the model (M/G/6)(GD∞/∞)From the calculation of the performance tables of several different servers, it has been found that the performance of the queuing system contained in the motorbike service is optimal using 5 servers. Testing the distribution of arrival time and customer service is carried out using SPSS.25 software.